Monday Club building payment no. 3 (1933)
Receipt and statement of contracts, payments, and deductions, issued by Julia Morgan to J. Jepson. The payment documented in this receipt amounts to $1,552.06, and was paid on an invoice from Pacific Coast Coal Company. Writing on the back indicates a discount should have been applied but was not.